Effects of diffusion of innovations, spatial presence, and flow on virtual reality shopping - Lu, Xiaojing; Hsiao, Kuo-Lun (Frontiers in Psychology, 2022)
Virtual reality (VR) has developed rapidly, drawing more businesses to such development. Based on the diffusion of innovations theory (DOI), the study combines the flow theory and the satisfaction perspective to explore purchase intention influencing customers' adoption of the VR shopping platform system. This study found that satisfaction and flow experience enhance their purchase intention. In technological characteristics, relative advantage, service compatibility, spatial presence, and complexity are important in satisfaction. Among them, both relative advantage and spatial presence impact flow experience. Additionally, a cluster analysis based on gender was conducted, and the study found a significant difference between relative advantages, service compatibility, and complexity in women and men users. The flow experience is an important factor affecting women users' shopping intention, while insignificant for male users. The implications of these findings are discussed.